2007
DOI: 10.1159/000252825
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Total Homocysteine Levels and Methylenetetrahydrofolate Reductase Gene Polymorphism in Patients with Type 2 Diabetes Mellitus

Abstract: Background: Thrombotic episodes account for approximately 80% of deaths in type 2 diabetic patients. Hyperhomocysteinaemia is a well recognized independent risk factor for atherosclerosis and thromboembolism. Increased homocysteine levels may occur due to a number of factors including inherited gene polymorphism of methylenetetrahydrofolate reductase (MTHFR) C677T. Here, we evaluate plas- ma total homocysteine (tHcy) levels and frequency of the MTHFR C677T gene polymorphism in asymptomatic healthy volunteers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 88 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Eleven studies (2498 T2DM) [ 12 , 25 , 30 , 31 , 35 , 38 , 39 , 48 - 50 ] were identified that satisfied inclusion criteria and expressed the between-group difference in plasma Hcy level in terms of the arithmetic mean and standard deviation. In all these studies, the mean Hcy concentration was greater in subjects with MTHFR 677TT than in those with the other two genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies (2498 T2DM) [ 12 , 25 , 30 , 31 , 35 , 38 , 39 , 48 - 50 ] were identified that satisfied inclusion criteria and expressed the between-group difference in plasma Hcy level in terms of the arithmetic mean and standard deviation. In all these studies, the mean Hcy concentration was greater in subjects with MTHFR 677TT than in those with the other two genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis published in 1998 concluded there was an association between the TT genotype and elevated plasma homocysteine levels in individuals with T2DM [17], while a more recent prospective study found no such association [72]. Thus, we second the conclusions of previous authors that the link between Hcy levels and T2DM remains unclear [48], [53], [56], [60]. The recommendation of the College of American Pathologists to measure Hcy only in patients with documented atherosclerotic disease [73] seems reasonable, given that HHcy is commonly accepted to be an independent risk factor for atherosclerosis and thromboembolism [74].…”
Section: Discussionmentioning
confidence: 60%
“…Most of the studies included in the present systematic review did not analyze Hcy levels in cases and controls, making it difficult to gain a comprehensive picture. Of the studies that did examine whether Hcy levels were associated with the rs1801133 polymorphism, 11 found the TT genotype to be associated with higher Hcy levels than the CT or CC genotypes in patients with T2DM [7], [8], [31], [32], [35], [45], [46], [51], [54], [59], [60], while 6 found no such association [27], [48], [49], [52], [56], [57]. A meta-analysis published in 1998 concluded there was an association between the TT genotype and elevated plasma homocysteine levels in individuals with T2DM [17], while a more recent prospective study found no such association [72].…”
Section: Discussionmentioning
confidence: 99%
“…After titles and abstracts screening, 81 nonrelevant records were excluded. The remaining 60 articles and eight additional articles identified from retrieved studies were included in the final meta‐analysis (Al‐Harbi et al, ; Al‐Salihi, Ajeena, Al‐Kashwan, & Al‐Lebban, ; Zidan, El Mougy, Moustafa, El attar, & Mohamed, ; Benrahma et al, ; Bluthner et al, ; Cao, Huang, Mao, & Gao, ; Chang et al, ; Chen, Ning, Zhu, Li, & Shi, ; Chen et al, ; P. Chen, Pan, Sun, Bai, & Fu, ; Dai & Yu, ; El Hajj Chehadeh et al, ; Eroglu et al, ; Errera et al, ; Fekih‐Mrissa et al, ; Fujita et al, ; Guo, Pan, Chu, Guo, & Sun, ; Guo et al, ; Hu, Zhang, Fang, Qin, & Liu, ; Hu, Gan, Li, & Bi, ; Jimenez‐Ramirez et al, ; Ksiazek, Bednarek‐Skublewska, & Buraczynska, ; Lin, Wang, & Liu, ; Liu et al, ; Luo, Yan, Li, Cheng, & Song, ; Luo, Yan, Ma, Cheng, & Song, ; Mao, Gao, Qin, & Shi, ; Mehri et al, ; Mei, Chen, & Zheng, ; Mtiraoui et al, ; Neugebauer, Baba, & Watanabe, ; Nithya et al, ; Odawara & Yamashita, ; Pirozzi et al, ; Qiu, ; Rahimi et al, ; Ramanathan, Harichandana, Kannan, Elumalai, & Sfd, ; Raza, Abbas, Siddiqi, & Mahdi, ; Settin, El‐Baz, Ismaeel, Tolba, & Allah, ; Shang, Wang, & Liu, ; Shi, He, Cheng, Wang, & Liu, ; J. Shi, Li, Yu, Chen, & Tao, ; Shpichinetsky et al, ; Soares et al, ; J. Sun, Xu, Xue, Zhu, & Lu, ; Sun, Xu, & Zhu, ; Sun, Xu, Zhu, & Lu, ; Sun, Xu, Lu, & Zhu, ; Sun, Chen, et al, ; Sun, Wang, Shi, & Yang, ; Wang et al, ; Wang, Hu, Xiao, & Wan, ; Wang, Wang, & Li, ; Wang, Wang, Xue, Chen, & Zou,…”
Section: Resultsmentioning
confidence: 99%